Correlation of Ghrelin and Obestatin with Waist Circumference in Central Obese Men - Widya Kurniawati; Marsetio Donosepoetro; Andi Wijaya (The Indonesian Biomedical Journal, 2011)
BACKGROUND: Central obesity is known as the cause of many metabolic disorders called Metabolic Syndrome. Accumulation of adipocytes in central obesity increases production of cytokines proinflammation. Free fatty acid increases in obesity that drives atherogenic dyslipidemia and insulin resistance. IDF 2005 states that waist circumference (WC) is regarded as the simple criteria of obesity. Energy imbalance lasting for a long period is a determinant factor for obesity, e.g. when energy intake is greater than energy expenditure. The brain and gastrointestinal tract work together to maintain this system. Ghrelin and Obestatin are two gut hormones that work in different ways to keep the energy balance. Ghrelin increases appetite but Obestatin decreases it. The two hormones play an important role in maintaining the dynamic equilibrium of energy balance. This study was aimed to determine correlation of Ghrelin and Obestatin with WC in central obese men.METHODS: This was a cross sectional study involving 53 central obese men. Based on IDF 2005 central obesity is most easily measured by waist circumference using the guidelines ethnic group (not country of residence) specific. We used South Asia ethnic which including Chinese, Malay and Asian Indian population as criteria for this study, that was WC >90 cm, aged 20-60 years. Subjects who had smoking habit, any infectious disease, and ACS were excluded from the study. No restriction was applied on the kind of meals the subjects were having or activities they were doing. The correlation of waist circumference with ghrelin and obestatin was assessed with a significance level of 95% (α=0,05).RESULTS: Patient's age was 40.9623±7.9080 year, waist circumferences was 102.1981±10.2696 cm, weight was 85.8679±16.5475 kg, height was 168.8066±6.3535 cm, BMI was 29.9723±2.4937 kg/m2. Concentration of Ghrelin were 0.70-13.72 ng/mL, and Obestatin 16.66-148.84 pg/mL. Pearson correlation showed that Ghrelin (r=-0.1114, p=0.4271) and Obestatin (r=-0.1781, p=0.2020) had no significant correlation with WC. But in patients WC ≥120 cm had significant negative correlation with Obestatin (r=-0.375, p=0.049).CONCLUSIONS: There was no significant correlation of Ghrelin and Obestatin with WC in obese men. However, there was a negative correlation tendency found in patients with greater WC (≥102 cm).KEYWORDS: obesity, ghrelin, obestatin, waist circumference (WC)